Engaging Generation Z through K-popfication: The Role of Buzz and Viral Marketing in Building MSME Brand Awareness - Fauziah Ibrahim; Popy Novita Pasaribu; Baiq Sakdiah; Hadi Azis Pratama; Muhamad Rizky; Lusita (Jurnal Manajemen, 2026)
Generation Z (Gen Z), born between 1997 and 2012, is a digital-native consumer group whose purchasing behavior is strongly shaped by cultural trends such as K-pop. For Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, reaching this demographic is crucial for building brand awareness but remains a challenge. Previous studies have discussed viral marketing and cultural branding separately, yet limited research has integrated buzz marketing, viral marketing, and K-popfication in one model. This study aims to examine how these strategies influence Gen Z consumers’ brand awareness of MSME products. A quantitative survey was conducted with 153 Gen Z respondents who actively use social media and have purchased MSME products. Data analysis used Structural Equation Modeling (SEM) with SmartPLS 4. The outer model confirmed convergent validity, discriminant validity, and construct reliability. The inner model produced an R² value of 0.690, indicating that the three strategies explained 69% of the variance in brand awareness. The results showed that buzz marketing had no significant effect, viral marketing had a positive but insignificant effect, while K-popfication had a strong and significant effect on Gen Z brand awareness.These findings highlight that Gen Z consumers are more responsive to cultural adaptation, especially through K-pop elements, than to conventional marketing approaches. Theoretically, this study enriches the Hierarchy of Effects framework in cultural marketing. Practically, it suggests that MSMEs should design campaigns that resonate with Gen Z’s digital habits and cultural identity to strengthen brand awareness.